2012
DOI: 10.1021/jp207679e
|View full text |Cite
|
Sign up to set email alerts
|

Study of Direct Synthesis of Hydrogen Peroxide Acid Solutions at a Heat-Treated MnCl–Porphyrin/Activated Carbon Cathode from H2 and O2

Abstract: Heat-treated MnCl−porphyrin supported on activated carbon (AC) catalyzed electrochemical reduction of O 2 to H 2 O 2 using an H 2 /O 2 fuel cell reactor. Suitable preparation conditions for an Mn−porphyrin electrocatalyst were studied for the H 2 O 2 formation, such as types of porphyrin rings, heat-treatment temperatures in He, and Mn loadings. The effects of reaction conditions, H 2 SO 4 concentration, P(O 2 ), P(H 2 ), and electrolyte flow on the H 2 O 2 formation were studied. Then, 0.5 wt % MnCl−TPP/AC he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…They also used graphitic carbon materials, vapor-grown carbon fibers (VGCF), 63 activated carbon with VGCF, 64 oxidized activated carbon with VGCF, 65,66 and metal-nitrogen/carbon (M-N/C) catalysts, Co-NX, [67][68][69] and Mn-NX. 71 Notably, several reports show that the oxidative treatment of carbon can yield higher rates of H2O2 production in a fuel cell configuration as well as in the electro-Fenton process. 51,65 Incorporating phenol groups onto carbon electrodes improves the rates of H2O2 production in a PEM electrolyser setup.…”
Section: Tailoring the Electrode; Fundamental Aspects Of The 2 Electrmentioning
confidence: 99%
See 1 more Smart Citation
“…They also used graphitic carbon materials, vapor-grown carbon fibers (VGCF), 63 activated carbon with VGCF, 64 oxidized activated carbon with VGCF, 65,66 and metal-nitrogen/carbon (M-N/C) catalysts, Co-NX, [67][68][69] and Mn-NX. 71 Notably, several reports show that the oxidative treatment of carbon can yield higher rates of H2O2 production in a fuel cell configuration as well as in the electro-Fenton process. 51,65 Incorporating phenol groups onto carbon electrodes improves the rates of H2O2 production in a PEM electrolyser setup.…”
Section: Tailoring the Electrode; Fundamental Aspects Of The 2 Electrmentioning
confidence: 99%
“…They tested 15 several different cathode catalysts, including vapor-grown carbon fiber (VGCF), 63 activated carbon with VGCF, 64 oxidized activated carbon with VGCF, 65,66 Co-NX, [67][68][69][70] and Mn-NX. 71 Using Co-NX/C as a cathode catalyst, Yamanaka and coworkers demonstrated that they could produce aqueous solutions of H2O2 at concentrations as high as 18.7 wt% H2O2, with a Faradaic efficiency of 55 %. 70 A key advantage of using the PEM configuration is that the H2O2 produced is H2O2 in pure water, as shown in Figure 6d.…”
mentioning
confidence: 99%
“…CV studies were also not effective to obtain information about the electrochemical active site because the electric double layer of AC was so large and no difference was found in the CV data of Mn(OEP)Cl/AC(T) and only AC 25) . However, significant information was obtained for the active site structure by temperatureprogrammed-desorption (TPD) spectra of Mn(OEP)Cl/ AC.…”
Section: Characterization Of the Mn-porphyrin/ac(t)mentioning
confidence: 99%
“…However, significant information was obtained for the active site structure by temperatureprogrammed-desorption (TPD) spectra of Mn(OEP)Cl/ AC. Desorption products from the Mn(OEP)Cl/AC 25) . At higher pyrolysis temperatures, the porphyrin ring structure of Mn(OEP)/AC decomposed and electrocatalysis at the Mn site changed from twoelectron reduction to four-electron reduction of O2.…”
Section: Characterization Of the Mn-porphyrin/ac(t)mentioning
confidence: 99%
“…The major roadblock in this method is the development of a sustainable electrocatalyst for the selective reduction of oxygen to H 2 O 2 [19][20][21][22][23]. Today, most electrochemical H 2 O 2 production methods rely on precious-metal-based materials or transition metal and/or metal oxides, and hence their economic viability for the future technologies is highly questionable [10,[24][25][26][27]. Hence new metal-free electrode materials for H 2 O 2 generation are highly sought after for future technologies.…”
Section: Introductionmentioning
confidence: 99%